Edukasi Gaya Hidup Sehat dan Pemeriksaan Profil Lipid sebagai Upaya Pencegahan Sindrom Metabolik pada Dewasa Produktif - Ernawati Ernawati; Alexander Halim Santoso; Bryan Anna Wijaya (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Metabolic syndrome is a global health concern that increases the risk of cardiovascular disease and type 2 diabetes mellitus, particularly among productive-age adults. This community program aimed to assess lipid profiles and enhance public awareness of healthy lifestyle practices as a preventive measure against metabolic syndrome. The activity was conducted at one private school, in Jelambar, West Jakarta using the Plan-Do-Check-Action (PDCA) approach, encompassing planning, biochemical screening, personalized education, and follow-up. Lipid profile assessments including total cholesterol, HDL, LDL, and triglycerides were performed using a point-of-care testing (POCT) method on 46 participants aged 20–63 (mean 42.36 ± 11.75 years). Results showed that most participants had normal lipid parameters: total cholesterol (67.4% normal), triglycerides (87% normal), HDL (100% normal), and LDL (91.3% optimal). Female participants had higher HDL levels, while males exhibited higher triglycerides, consistent with physiological variations influenced by sex hormones. The educational intervention effectively improved participants’ understanding of the relationship between dyslipidemia, diet, physical activity, and metabolic risk. This study highlights that combining lipid profile screening with healthy lifestyle education is an effective, practical, and applicable promotive–preventive strategy to reduce the risk of metabolic syndrome and strengthen routine health screening behavior among productive adults.